Phylodynamics of the Emergence of Influenza Viruses after Cross-Species Transmission - Rahnama, Leila (Public Library of Science, 2013)
Human populations are constantly exposed to emerging pathogens such as influenza A viruses that result from cross-species transmissions. Generally these sporadic events are evolutionary dead-ends, but occasionally, viruses establish themselves in a new host that offers a novel genomic context to which the virus must adjust to avoid attenuation. However, the dynamics of this process are unknown. Here we present a novel method to characterize the time it takes to G+C composition at third codon positions (GC3 content) of influenza viruses to adjust to that of a new host. We compare the inferred dynamics in two subtypes, H1N1 and H3N2, based on complete genomes of viruses circulating in humans, swine and birds between 1900–2009. Our results suggest that both subtypes have the same fast-adjusting genes, which are not necessarily those with the highest absolute rates of evolution, but those with the most relaxed selective pressures. Our analyses reveal that NA and NS2 genes adjust the fastest to a new host and that selective pressures of H3N2 viruses are relaxed faster than for H1N1. The asymmetric nature of these processes suggests that viruses with the greatest adjustment potential to humans are coming from both birds and swine for H3N2, but only from birds for H1N1.